Personification in Oscar Wilde’s "The Selfish Giant" - Adhikari, Bhawani Shankar (Kutumbha vani, 2024)
The research has displayed the role of the literary figure of speech, personification used in the story of Oscar Wilde’s "The Selfish Giant". It has linked the four types of the personifications and how the British women have been applied as the personifications to extend the colonial government as the civilized and the superior race in the globe. As the British women have been found to be powerful to the British colonial government, so is the strength of the use personifications in the work of art and in the literary creativity. The personified objects and the seasons in the story have elevated its classic form to the fairy-tale as the story of the children and it has lured the attention of the readers. Reading such personified tales enhances the creativity of the children and of any readers but it is to be identified as the language of personifications by the readers while reading it. The beauty and the strength of the fairy-tale would be lost in absence of the personified objects and the seasons in the story "The Selfish Giant". Overall, personification in “The Selfish Giant” makes the story’s moral lessons more accessible and memorable for children by giving human traits to non-human elements and depicting their interactions in a way that resonates with the readers’ own experiences and emotions. While younger children might understand personification more through the narrative and illustrations, older children might analyze it more critically and recognize it as a literary device used to enhance the story’s themes and moral lessons. It has been found that the teachers have to apply some of the techniques in the context for the students in making them comprehending the use of the personification in the story and by displaying the effectiveness of the use of the figure of speech in creating the curiosity for the learners.